Guru agama Kristen Sebagai Teolog Praktika Garis Depan Bagi Siswa - Sostenis Nggebu (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The purpose of this article is to discuss that Christian teachers have an important role in passing on theological concepts to students. This study uses a descriptive method. The result is that Christian teachers become theologians because they carry out their function as teachers in the field of practical theology for students (cf. Eph 4:11-14; Jas 3:1). They are called theologians because the source of their teaching comes from the Scriptures and contributes to the development of a theological framework based on the leading of the Holy Spirit (cf. Jn 14-16). Practically, Christian teachers formulate beliefs or theological arguments that can be used as a reference to build the spiritual life of students so that they know God and love Him through Jesus Christ.